2021
DOI: 10.1002/fsn3.2299
|View full text |Cite
|
Sign up to set email alerts
|

Health benefits of docosahexaenoic acid and its bioavailability: A review

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(46 citation statements)
references
References 166 publications
(211 reference statements)
0
43
0
3
Order By: Relevance
“…As indicated by our results, diets containing Cr and SBL increased the concentrations of C22:5 n-3 (DPA), C22:6 n-3 (DHA), and n-3 PUFA in the thigh muscles of chickens compared with the control treatment (T0). This trend of improving DHA content in meat is important because it is essential for brain tissue growth and function, especially during development and infancy [ 55 ], reduces the incidence of cardiovascular disease and preterm birth, protects against allergies, boosts immunity, and improves cognitive function [ 56 ]. A poultry product enriched with DHA that redresses nutritional imbalances in today’s diet and meets associated nutritional health requirements is attractive to the modern, educated consumer [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As indicated by our results, diets containing Cr and SBL increased the concentrations of C22:5 n-3 (DPA), C22:6 n-3 (DHA), and n-3 PUFA in the thigh muscles of chickens compared with the control treatment (T0). This trend of improving DHA content in meat is important because it is essential for brain tissue growth and function, especially during development and infancy [ 55 ], reduces the incidence of cardiovascular disease and preterm birth, protects against allergies, boosts immunity, and improves cognitive function [ 56 ]. A poultry product enriched with DHA that redresses nutritional imbalances in today’s diet and meets associated nutritional health requirements is attractive to the modern, educated consumer [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…A poultry product enriched with DHA that redresses nutritional imbalances in today’s diet and meets associated nutritional health requirements is attractive to the modern, educated consumer [ 57 ]. The current research is already taking steps to deepen the topic of meat enrichment with LC-PUFA, especially DHA, because according to current data, the bioconversion rate of ALA (abundant in vegetable oils) to DHA in the human body is extremely low [ 56 ], with most of ALA β-oxidized, and therefore DHA-rich foods and DHA supplements are the two main exogenous sources used to obtain additional DHA needed for the biological functions of the human body. In addition, the current study found that Cr and SBL supplemented diets effectively converted ALA to DHA, which cannot be synthesized in the body but is required for maintaining optimal human health and nutrition, and its storage in selected tissues (breast and thigh).…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, several studies have looked specifically at microalgal n-3 LC-PUFA in oil form and have demonstrated that PUFA are both taken up and have beneficial effects in the body (Lane et al, 2014;Li et al, 2021); intake of microalgal DHA (0.2-1.0 g/day) over 4 weeks resulted in a dosedependent increase in the DHA content of plasma and erythrocyte lipids, and reduced ARA levels in the same tissues (Arterburn et al, 2007). Likewise, consumption of 0.94 to 1.5 g microalgal DHA/day over 4 to 8 weeks doubled plasma DHA content and reduced plasma TG by 14 to 23% at the end of the studies (Geppert et al, 2006;Sanders et al, 2006), with best effects in patients with the highest triglyceridemia (Geppert et al, 2006).…”
Section: Composition Of Algae Oilsmentioning
confidence: 99%
“…Dietary adjustments, such as increasing DHA intake or consuming foods rich in flavonoid, can help lower cholesterol and reduce the incidence of AD [ 18 , 19 ]. Oral DHA supplementation in animal tests has been shown to lessen the progression of Alzheimer’s-like brain degeneration [ 20 ]. Germinated brown rice (GBR) has numerous bioactives that contribute to its antioxidant effects [ 21 ].…”
Section: Introductionmentioning
confidence: 99%